(untitled) (Global Journal of Human-Social Science, 2017)
The need to feed livestock of herdsmen necessitates their migration from their communities due to inadequate pastures to other communities and this has led to the trespass of these pastoralists to the farmlands of local agriculturalists and destruction of their crops thereby leading to conflict This study therefore analyses the causes evolution dynamics and solutions to the conflicts generated from the farmers-herdsmen clashes in Nigeria The study also recommends the formulation of national livestock development policy effective community policing model demarcation of livestock grazing reserves provision of constitutional roles and recognition for traditional rulers and convening of stakeholders conference on nomadic pastoralism as strategies for ensuring peace